New lactone and isocoumarin derivatives from the marine mangrove-derived endophytic fungus Penicillium coffeae MA-314. (August 2019) - Cao, Jin; Li, Xiao-Ming; Li, Xin; Li, Hong-Lei; Meng, Ling-Hong; Wang, Bin-Gui
Graphical abstract: Highlights: The first report on the natural products from the fungus Penicillium coffeae . A new δ -lactone (1 ) and two pairs of new isocoumarin derivatives (2 and3 ) were isolated. Penicoffeazine A (1 ) showed inhibitory activity against two plant-pathogenic fungi. Abstract: A new δ -lactone (penicoffeazine A, 1 ) and two pairs of new isocoumarin derivatives (penicoffrazins B and C, 2 and3 ), along with five known isocoumarin derivatives (4 −8 ), were isolated from Penicillium coffeae MA-314, an endophytic fungus obtained from the fresh inner tissue of the leaf of marine mangrove plant Laguncularia racemosa . The structures of all these compounds were elucidated by spectroscopic analysis and the absolute configuration of compound1 was determined by ECD experiments and compared with that of calculated ECD spectrum. The relative configurations of compounds2 and3, which were two pairs of enantiomers, were confirmed by NOESY experiments. Compound1 was tested for antibacterial activity and the other compounds were tested for antioxidant activity. This is the first report on the natural products of the fungus Penicillium coffeae .